Diagnostic Accuracy of H. pylori Status by Conventional Endoscopy: Time-Trend Change After Eradication and Impact of Endoscopic Image Quality - Quach, Duc Trong; Aoki, Rika; Iga, Akiko; Le, Quang Dinh; Kawamura, Toru; Yamashita, Ken; Tanaka, Shinji; Yoshihara, Masaharu; Hiyama, Toru (Frontiers in Medicine, 2022)
AIM: To assess the time trend of diagnostic accuracy of pre- and post-eradication H. pylori status and interobserver agreement of gastric atrophy grading. METHODS: A series 100 of conventional endoscopic image sets taken from subjects undergoing gastric cancer screening at a polyclinic were evaluated by 5 experienced assessors. Each assessor independently examined endoscopic findings according to the Kyoto classiﬁcation and then determined the H. pylori status (never, current, or past infected). Gastric atrophy was assessed according to the Kimura-Takemoto classification and classified into 3 grades (none/mild, moderate, or severe). The image series that ≥3 assessors considered to have good quality were arbitrarily defined as high-quality image (HQI) series, and the rest were defined as low-quality image (LQI) series. RESULTS: The overall diagnostic accuracy of H. pylori status was 83.0%. It was lowest in subjects with current infection (54%), gradually increased at 1 year (79%, P <0.001) and 3 years (94.0%, P = 0.002), but then did not significantly change at 5 years (91.0%, P = 0.420) after eradication. The diagnostic accuracy of the LQI series was 28%. The overall diagnostic accuracy of H. pylori status dropped from 88.9% to 67.9% (P <0.001), and the mean kappa value on gastric atrophy grading dropped from 0.730 to 0.580 (P = 0.002) in the HQI and LQI series, respectively. CONCLUSIONS: Diagnostic accuracy of H. pylori status increased over time after eradication. LQI series badly affected the diagnostic accuracy of H. pylori status and the level of agreement when grading gastric atrophy.